CESifo World Economic Survey February 2016 - Johanna Garnitz; Gernot Nerb; Klaus Wohlrabe; Dorine Boumans (CESifo World Economic Survey, 2016)
World Economic Climate: World economic climate continues to cloud over - Economic Expectations: Economic expectations less positive - Inflation: Inflation set to edge upwards - Currencies: US dollar will gain strength - Interest Rates: Expectations of interest rate increase remain moderate - Special Topic: The impact of terrorism on the world economy
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies